English: Perilaku Pembelian Konsumen Pengguna Aplikasi Online Food Delivery (OFD) - Perangin-Angin, Fini Anjela; Simanjuntak, Megawati; Taryana, Asep (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
The high demand for food access with applications creates competition between food delivery companies. The purpose of this research is to identify and to analyze promotion differences, price value, social influence, perceived usefulness, ease of use, customer experience, restaurant search, choice of food variants, consumer buying behavior, and continuous purchase intention. The research was conducted on consumers who used Gofood, Grabfood, and Shopeefood applications at least once in the last three months, with 400 respondents aged over 15 years. Data collection was carried out using an online questionnaire. Analysis was carried out by descriptive analysis, ANOVA and SWOT tests. The results showed that there were differences in the variables of social influence, perceived usefulness, ease of use, restaurant search, food choice variants, consumer buying behavior, and intention to continue with Gofood, Grabfood, and Shopeefood applications. Shopeefood earns a lower average than Grabfood and Gofood. Strategies can be carried out by taking advantage of busy consumers to create dependence on OFD applications by meeting consumer expectations by providing promos.